Technology of decision-making in process management of the non-productive sphere - O. M. Kulikova (Вестник СибАДИ)
The article describes author's technology of acceptance of administrative decisions in process management in non-production sphere that contains two algorithms: the algorithm of detecting patterns and forecasting, algorithm development management decisions in the form of options. This technology allows you to create solutions in the form of the many features implemented or unrealizable for the given parameters of external and internal environments of control processes, making it possible to carry out process management under uncertainty and risk.